جماليّة القصيدة-الصّورة في شعر "سليمان جوّادي" - الحاج دواجي, عبد القادر; بوقربة, الشيخ (جامعة الوادي - University of Eloued, 2021)
تتناول الدّراسة جماليّة القصيدة-الصّورة في شعر "سليمان جوّادي" من زاوية تلقّيها وتفاعل القارئ معها، وهي دراسة تهدف أوّلاً إلى تصحيح المفهوم النّقدي للقصيدة-الصّورة، وإلى بيان حدودها وخصائصها الشّعريّة، ومحاولة دراسة تمثّلاتها في شعر "سليمان جوّادي"، وإبراز تأثير استخدام هذه القصيدة في عمليّة تلقّي شعره، وقد عمدنا إلى انتخاب نماذج من شعر "سليمان جوّادي" تمثّل القصيدة-الصّورة عنده بغية دراستها من زاوية تلقّيها ولمعرفة جوانب تأثير شعره على المتلقّي. The study deals with the aesthetic of the poem-image in the poetry of 'Suleiman Jawadi' in terms of its reception and the reader's interaction with it. The study aims first to correct the critical concept of the poem-image, and second, to identify its limits and poetic characteristics, and to try to study its representations in the poetry of "Suleiman Jawadi" in order to highlight the impact of using this poem on the process of receiving his poetry. To achieve this, we have chosen models from the poetry of 'Suleiman Jawadi' that represent the poem-image for him in order to study it from the angle of its reception and to know the aspects of the impact of his poetry on the recipient.
مقال
Keywords: جماليّة، القصيدة-الصّورة، "سليمان جوّادي"، أفق التّوقّع، التّلقّي، القارئ; aesthetics, poem-image, 'Suleiman Jawadi', horizon of expectation, reception, reader